Application of biological products in strawberry cultivars to control Botrytis cinerea (Research, Society and Development, 2021)
The objective of this work was to evaluate three strawberry cultivars in an organic production system combined with the application of biological products via leaf for the control of Botrytis cinerea aiming at increasing fruit productivity and quality. The experimental design was randomized block, in a 5x3 factorial scheme, consisting of four products and three cultivars. The treatments consisted of the biological products Onix (Bacillus methylotrophicus), Quartz (Bacillus amyloliquefaciens), Botector (Aureobasidium pullulans), Prestop (Gliocladium catenatum) and control (water application in the plot) in combination with three strawberry cultivars (Cristal, Monterey and Pircinque). Through the results it was possible to observe the superiority of the cultivar Cristal in the total fruit production when compared to the cultivars Monterey and Pircinque. The biological products Onix, Quartz and Botector provided higher total strawberry production. The recommended cultivar for planting in the southern region of Minas Gerais is Pircinque due to the high levels of soluble solids and total sugars observed. The application of biological products was effective in controlling Botrytis cinerea.